AL-‘AWĀMIL AL-NAḤWIYYAH: THEORY, DEBATES, AND MODERN CRITIQUES OF THE CONCEPT OF 'AMIL ( العامل والمعمول) - Marsyanti; Hamzah; Sri Mulya Nengsi (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The study of al-ʿawāmil al-naḥwiyyah (grammatical factors) serves as a primary foundation in Arabic grammar, examining the relationship between the ʿāmil (governing agent) and the maʿmūl (governed element) as the mechanism determining iʿrāb (inflection) within Arabic sentence structures. This article aims to comprehensively analyze the classical theory of the ʿāmil concept as formulated by early grammarians—notably al-Jurjānī in Al-ʿAwāmil al-Mi’ah—and examine the debates emerging between the Basra and Kufa schools regarding the source and authority of the ʿāmil. Utilizing a qualitative-descriptive analytical approach toward primary and secondary literature, this research explores the epistemological arguments underlying the construction of the ʿāmil theory and assesses its relevance to modern critiques in Arabic linguistics. The findings indicate that the ʿāmil concept is not merely a grammatical instrument but also possesses philosophical value in explaining the order and rationality of the Arabic language. However, modern critiques—particularly from structural and generative linguistic perspectives—question the metaphysical assumptions of the ʿāmil concept, which are deemed non-empirical. Nonetheless, the theory of ʿāmil maintains methodological significance in understanding Arabic syntactic relationships and the development of contemporary grammatical theories. This article emphasizes the necessity of a conceptual reinterpretation of al-ʿawāmil al-naḥwiyyah to remain relevant within modern linguistic paradigms without losing its classical essence.